A new genus and new species of potamid crab from Yunnan, southern China (Decapoda: Brachyura: Potamidae: Potamiscinae). Issue 1 (3rd March 2022) - Shi, Bo-Yang; Pan, Da; Sun, Hong-Ying
Abstract: A new genus and new species of freshwater crab, Barbamon zhoui gen. nov., sp. nov., belonging to the subfamily Potamiscinae Bott, 1970 (Potamidae Ortmann, 1896) is described from Wenshan Zhuangzu and Miaozu Autonomous Prefecture, Yunnan Province, China. The new genus is established based on a unique combination of characters, including the distinctive shape of the male first gonopod, and the setose ventral surface of the third maxilliped, suborbital and pterygostomial regions, and ambulatory legs. Barbamon gen. nov. is similar in external appearance to Abormon Mitra, Pati & Ng, 2021 . The new genus, however, is distinctive in the combination of characters related to the carapace, third maxilliped, and male first gonopod. Molecular phylogenetic data derived from mitochondrial 16S rDNA sequences provides genetic support for the new genus and species.